2015
DOI: 10.5539/ijbm.v10n2p1
|View full text |Cite
|
Sign up to set email alerts
|

A Global Investigation of Government and Community Stakeholder Influences on Large Company Engagement in Sustainability

Abstract: Business organizations are increasingly expected to address sustainability issues and to disclose socially responsible behaviors accurately and transparently, showing that they are effective at managing and being proactive about sustainability challenges. Stakeholder theory was used as a framework to investigate whether influence effects from two institutional stakeholder types were associated with the levels of strategic engagement in sustainability for large publicly listed firms in twenty five countries. Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…The study data indicated the lack of dialogue was an implicit barrier between business and both WSA and WSB relating to participation and adoption of the TBL. Citizen advocacy was a primary justification for the firm to use dialogue processes as a method to resolve conflicting TBL issues (Nemetz, 2015). Study data confirmed WSA and WSB used citizen advocacy to focus public attention on their agendas.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The study data indicated the lack of dialogue was an implicit barrier between business and both WSA and WSB relating to participation and adoption of the TBL. Citizen advocacy was a primary justification for the firm to use dialogue processes as a method to resolve conflicting TBL issues (Nemetz, 2015). Study data confirmed WSA and WSB used citizen advocacy to focus public attention on their agendas.…”
Section: Resultsmentioning
confidence: 59%
“…The value of this study to business is new insight for engaging communities by applying the TBL to CSR engagement strategies. Potential outcomes, confirming Nemetz's (2015) view, are: business may gain competitive advantage, enhance reputation, demonstrate responsible citizenship, and avoid coercive regulations. Also, this study should be of interest to executive directors of NGO's, especially those organizations that have strong environmental orientations.…”
Section: Importance Of the Studymentioning
confidence: 73%
See 1 more Smart Citation
“…11, No. 7; instruments for enhancing the sustainability of the financial system with increasing focus on the risk and opportunities related to the environment, social and governance (ESG) matters (UNPRI, 2014;PwC & Waterman, 2014;Nemetz, 2015). The literature on corporate sustainability has emphasized the growing role of ESG risks involved in investment decisions which has resulted in subsequent growth in sustainability accounting frameworks in recent years (Brown et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Service production and delivery once managed in-house, including environmental functions, are now often farmed out to private or nonprofit contractors (Bogason 1996; Brown and Potoski 2005). Even in the governments where the in-house direct provision remains the dominant paradigm, contracting or commissioning takes a very strong second place (Hefetz and Warner 2004, 2012; Nemetz 2015; Warner and Hebdon 2001). As a result, local residents commonly receive sustainability-related services from various vendors, including private companies, nonprofit organizations, and other jurisdictions’ public agencies (Krause et al 2019; Stokan and Deslatte 2019).…”
Section: Research Hypothesesmentioning
confidence: 99%